APLIKASI SISTEM INFORMASI GEOGRAFIS OBJEK WISATA BERBASIS MOBILE ANDROID PADA DINAS KEPEMUDAAN, OLAHRAGA DAN PARIWISATA (BIDANG PARIWISATA) KOTA METRO - Bunga Ridho Eldita; Didik Kurniawan; Febi Eka Febriansyah (Jurnal Komputasi, 2018)
Metro City is one of the second largest cities in Lampung Province. The city has several tourist spots that can be visited by tourists, but not all places in Metro city is known by tourists because less information to introduction of tourist attractions. Rapid technological developments is the human need for information on where the object of tourism demanded the availability of appropriate information systems, therefore geographic information systems based on Android mobile was developed. Agency Of Weekly, Sports And Tourism (Tourism Sector) in Metro City can also promote the potential of the region. Geographic information system of tourist attraction based Android mobile is one of the important things that every city needs to have that, with the application can improve the image of easy access to information. System development method in this research using XP (Extreme Programming). In this application the user can see the map of the spread on attractions place in Metro city and can see information about each place a tourist attraction equipped with travel routes. Application testing technique using Black-Box Testing method is Equivalance Partitioning. The results of research data using a user questionnaire can be concluded that the application get a percentage value of 89.06% belonging to the category very well.